Spotlighting Nigeria’s New Health Agenda: A Case Study on the Alignment of Global Health Initiatives with National Health Priorities Through the SRMNCAEH+N Lens - Pitan, Oyeyemi; Ade-Banjo, Olympus; Joseph, Esther; Aboiyar, Torna; Adomi, Solomon (British Journal of Healthcare and Medical Research, 2025)
Background: Alignment of global health initiatives (GHIs) with national health priorities is crucial for effective and sustainable healthcare interventions and strengthening health systems. Despite widespread recognition of this need, achieving alignment between GHIs and national priorities has proven challenging. The importance of addressing this challenge has led to a growing focus on GHIs alignment, evident in forums such as the Paris Conference in 2015 and the Lusaka Agenda in 2023. As Nigeria embarks on a new mid-term health agenda based on the sector-wide approach (SWAp), understanding the country-level implications of alignment becomes paramount. Method: This study utilized qualitative research methods to examine the issues affecting GHI alignment within the context of the sexual, reproductive, maternal, neonatal, adolescent, elderly, nutrition health plus nutrition (SRMNCAEH+N) program. Through 24 interviews and focus group discussions with key stakeholders including government officials, representatives of global health institutions, civil society actors, health workers, and community members, this research identified and validated six critical issues influencing GHI alignment at the country level. Result: The findings shed light on current practices, challenges, and recommendations, highlighting Nigeria's readiness to implement the new health agenda and SWAp effectively. The research identified and validated six critical issues influencing GHI alignment at the country level through the perspectives of diverse stakeholders. Conclusion: The paper underscores the importance of extensive stakeholder involvement, including communities, in achieving optimal alignment between GHIs and national health priorities. The study's insights into the alignment dimensions of Nigeria’s SRMNCAEH+N program reveal key areas for improvement and collaboration, essential for the successful implementation of Nigeria's new health agenda.